Lactobacillus johnsonii modulation of bone marrow-derived dendritic cells generated from mice with null mutation of the Muc2 gene - E. A. Blinova; E. P. Goncharova; G. V. Kalmykova; N. I. Akulova; E. A. Litvinova (Медицинская иммунология, 2023)
The gut is inhabited by a trillion bacteria that produce up to 60% of the host’s metabolites. The gut microbiome plays an important role in regulating host immune function. A lot of research concerned the effect of probiotic on the pathologies associated not only with dysbiosis and metabolic disorders, but there is breakthrough in the treatment of inflammation, oncology and neurodegenerative disorders. Animals with mutation of the genes leading to pathology used to assay probiotic effect. To understand direct action of probiotics, cells derived from control mice or cell culture of tumor genesis in vitro studies are used. However, there is little research of the probiotic effect on cells derived from mice with pathology. In this study, we assessed the phenotypes of dendric cells derived from Muc2-/- mice with chronic inflammation and assessed the effect of L. johnsonii on the dendric cells. It is known that the key features of IBD models are thinning of mucin layer and changes in the intestinal microbiome. We compared the efficiency of maturation and activation of dendric cells derived from the bone marrow of Muc2-/- mice and dendric cells obtained from healthy C57BL/6 mice free from specific species pathogens. We evaluated the expression of co-stimulatory molecules, the proliferative index, and the ability to trigger the T regulatory response of dendric cells, which were stimulated with the probiotic L. johnsonii. Markers of dendritic and T cells were assessed by flow cytometry using antibodies to extra- and intracellular proteins. The proliferative activity of splenocytes was assessed using the WST test. It was shown that dendric cells derived from the Muc2-/- had an immature phenotype. Dendric cells of Muc2-/- mice could not effectively stimulate the proliferation of allogeneic and syngeneic T cells. L. johnsonii was able not only to stimulate the maturation of dendric cells derived from Muc2-/- mice, but also to increase the expression of FoxP3 on CD25+ T cell that were co-cultured with DCs. Thus, we believe that this probiotic bacterium can reduce signs of inflammation and reduce pathological processes in animals of an experimental model of IBD in vivo.